2004
DOI: 10.1111/j.1365-2133.2004.06047.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs' micrographic surgery for treatment of basal cell carcinoma of the face--results of a retrospective study and review of the literature

Abstract: Based on the fact that MMS provides the lowest recurrence rates, it is the treatment of first choice for primary facial BCCs with an aggressive histopathological subtype and for recurrent BCCs in the face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
197
2
27

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(237 citation statements)
references
References 40 publications
11
197
2
27
Order By: Relevance
“…The main advantage of such an approach is the one-stage tumor excision in clear margins, while the disadvantages are its being time-consuming and patient discomfort. A previous study (20) using a large patient cohort investigated the long-term outcome of Mohs micrographic surgery for basal cell carcinomas of the face. Results of that study demonstrated a 5-year recurrence rate of 4.5% for the lesions, 3.2% for primary tumors and 6.7% for recurrent ones.…”
Section: Frozen Section ---------------------------------------------mentioning
confidence: 99%
“…The main advantage of such an approach is the one-stage tumor excision in clear margins, while the disadvantages are its being time-consuming and patient discomfort. A previous study (20) using a large patient cohort investigated the long-term outcome of Mohs micrographic surgery for basal cell carcinomas of the face. Results of that study demonstrated a 5-year recurrence rate of 4.5% for the lesions, 3.2% for primary tumors and 6.7% for recurrent ones.…”
Section: Frozen Section ---------------------------------------------mentioning
confidence: 99%
“…The most frequently recurrences (70.3%-80.0%) are revealed as well as with after other methods of therapy of skin carcinomas; it ranges from 70.0 % to 82.4 % during the first year of monitoring [2,3,7,9]. A low percentage of facial carcinoma recurrences after laser treatment might be explained by the deeply penetrating laser energy [21] so that was possible to impact on the entire tumor mass.…”
Section: Discussionmentioning
confidence: 99%
“…However treatment of skin carcinomas localized on the face presents difficulties due to the complex anatomy of the area, which localized on the face approximately in 79.6-90.6% patients [3]. The use of above mentioned methods for the treatment of facial carcinoma results in tumor recurrence in 1.6-9.5% patients [3][4][5][6][7][8][9][10]. The progress in treatment of skin carcinoma has been achieved after laser radiation was introduced into practice [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Primer lezyonda, 5 yıllık kür oranları %94 ile %99 arasında değişmektedir [26][27][28] . Mohs cerrahisinin başlıca endikasyonları 2 cm.den büyük, rekürren, yüksek risk içeren alanlarda BHK bulunması, periorbital, paranazal gibi geniş sınırlarla eksizyonun zor olduğu alanlarda BHK bulunması yer almaktadır 6 .…”
Section: Bhk Tedavi Seçenekleri Ve Güncel Yaklaşımlarunclassified